Method for preparing low-cost sodium titanate negative electrode material from titanyl sulfate solution
Metatitanate is prepared by hydrolysis of titanium sulfate solution and sodium titanate is calcined with sodium source, which solves the problem of high production cost of sodium titanate anode material and realizes the preparation of low-cost and high-performance sodium titanate anode material.
Patent Information
- Application Number
- CN202411427162.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-14
AI Technical Summary
The production cost of existing sodium titanate anode materials is high, which limits its application in sodium ion batteries.
Metatitanic acid is prepared by hydrolysis of titanium sulfate solution, and then calcined with sodium source to prepare sodium titanate, omitting the calcination, surface treatment, impurity removal and other links from metatatic acid to titanium dioxide, reducing production costs.
The low-cost preparation of sodium titanate negative electrode material has been achieved. The specific capacity of the product reaches 82mAh/g at 2000mA/g, and the capacity retention rate of 1,000 cycles reaches more than 78.4%, and the performance is excellent.
Smart Images

Figure CN119390112A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a method for preparing a low-cost sodium titanate negative electrode material from a titanyl sulfate solution. Background Art
[0002] With the increasing global demand for renewable energy, energy storage technology has become the key to achieving energy transformation and ensuring energy security. Among the many energy storage technologies, sodium-ion batteries are gradually becoming a powerful supplement to lithium-ion batteries due to their advantages such as abundant resources, low cost and potential high energy density, especially in the field of large-scale energy storage. However, graphite, the negative electrode material widely used in lithium-ion batteries, is limited in its application in sodium-ion batteries due to ion size mismatch and interlayer spacing issues. Therefore, researchers are exploring other types of negative electrode materials. Among them, sodium titanate is very suitable for large-scale energy storage due to its environmental friendliness and safety, and has received widespread attention and research in recent years.
[0003] However, the synthesis methods of sodium titanate materials reported so far are mostly limited to hydrothermal method, sol-gel method, etc. In addition, the raw materials are mostly titanium metal, tetrabutyl titanate, etc. The high production cost and the inability to scale up production have restricted the commercialization progress of sodium titanate materials.
[0004] Existing methods for preparing sodium titanate negative electrode materials generally use titanium metal, tetrabutyl titanate, titanium dioxide and other substances as titanium sources, resulting in high production costs of sodium titanate negative electrode materials, which limits the application of sodium titanate negative electrode materials. How to prepare low-cost sodium titanate negative electrode materials has become a technical problem that needs to be solved urgently. Summary of the Invention
[0005] In order to solve the technical problem of high production cost of existing sodium titanate negative electrode materials, the present invention provides a method for preparing low-cost sodium titanate negative electrode materials from titanyl sulfate solution.
[0006] The present invention is a method for preparing a low-cost sodium titanate negative electrode material from a titanyl sulfate solution, the preparation method comprising the following steps:
[0007] S1. Preheating of base liquid: Take an appropriate amount of deionized water in the reactor and preheat it to 80℃-110℃;
[0008] S2. Hydrolysis: Add the titanyl sulfate solution to the reactor at a uniform rate while stirring, and keep the temperature of the system in the reactor constant. The hydrolysis reaction ends when the feeding is completed;
[0009] S3. Preparation of metatitanic acid: Cooling the hydrolyzed slurry to room temperature, washing with water, and drying to obtain metatitanic acid;
[0010] S4. Preparation of sodium titanate: uniformly mixing a sodium source and metatitanic acid in a sodium to titanium molar ratio of 2:3, calcining under an argon atmosphere, and then naturally cooling to obtain sodium titanate.
[0011] Furthermore, the stirring speed in step S2 is 1000-1400 rpm.
[0012] Furthermore, the concentration of the titanyl sulfate solution in step S2 is 170-240 g / L.
[0013] Furthermore, in step S2, the feeding rate of the titanyl sulfate solution is 1.0-1.8 mL / min.
[0014] Furthermore, during the addition process in step S2, the system temperature is kept constant at 80°C-110°C.
[0015] Furthermore, the feeding time of the titanyl sulfate solution in step S2 is 2-12 hours.
[0016] Furthermore, in step S3, the drying temperature is 120° C. and the drying time is 10 hours.
[0017] Furthermore, in step S4, the sodium source is one or more of sodium acetate, sodium carbonate, sodium hydroxide, sodium oxalate, sodium oxide, and sodium peroxide.
[0018] Furthermore, the calcination in step S4 is as follows: heating to 800-950° C. at a heating rate of 5° C. / min and keeping the temperature for 5-15 hours.
[0019] The present invention prepares metatitanic acid by hydrolyzing a titanyl sulfate solution, and then prepares sodium titanate by reacting the metatitanic acid with a sodium source. The sodium titanate prepared by the present invention has low cost and a simple and easy process. The sodium titanate has a specific capacity of more than 82 mAh / g at 2000 mA / g, a capacity retention rate of more than 78.4% after 1000 cycles, and excellent product performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a SEM spectrum of metatitanic acid, a hydrolysis product in Example 1 of the present invention;
[0021] Figure 2 This is the XRD spectrum of metatitanic acid, the hydrolysis product in Example 1 of the present invention;
[0022] Figure 3 This is a SEM spectrum of sodium titanate prepared in Example 1 of the present invention;
[0023] Figure 4 This is the XRD spectrum of sodium titanate prepared in Example 1 of the present invention;
[0024] Figure 5Performance diagram of the sodium titanate negative electrode prepared in Example 1 of the present invention after 200 cycles at 200 mA / g;
[0025] Figure 6 This is a performance diagram of the sodium titanate negative electrode prepared in Example 1 of the present invention after 1000 cycles at 2000 mA / g;
[0026] Figure 7 This is a rate performance diagram of the sodium titanate negative electrode prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention are within the scope of protection of the present invention.
[0028] Example 1
[0029] A method for preparing a low-cost sodium titanate negative electrode material from a titanyl sulfate solution, the preparation method comprising the following steps:
[0030] S1. Preheating of base liquid: Take an appropriate amount of deionized water in the reactor and preheat it to 80°C;
[0031] S2. Hydrolysis: Under stirring at 1000 rpm, a 170 g / L titanyl sulfate solution was uniformly added to the reactor at a feeding rate of 1.8 mL / min, and the temperature of the reactor was kept constant at 80° C. The feeding time was 2 h. The hydrolysis reaction ended when the feeding was completed;
[0032] S3. Preparation of metatitanic acid: Cool the hydrolyzed slurry to room temperature, wash with water, and dry at 120° C. for 10 h to obtain metatitanic acid;
[0033] S4. Preparation of Sodium Titanate: Sodium oxalate and metatitanic acid were mixed in a sodium to titanium molar ratio of 2:3. The mixture was calcined under an argon atmosphere at a heating rate of 5°C / min to 800°C, held for 15 hours, and then naturally cooled to obtain sodium titanate. The synthesized sodium titanate had a particle size of 6-10 microns and excellent sphericity. The sodium titanate achieved a specific capacity of 82 mAh / g at 2000 mA / g, with a capacity retention rate of 78.4% after 1000 cycles.
[0034] Example 2
[0035] A method for preparing a low-cost sodium titanate negative electrode material from a titanyl sulfate solution, the preparation method comprising the following steps:
[0036] S1. Preheating of base liquid: Take an appropriate amount of deionized water in the reactor and preheat it to 90°C;
[0037] S2. Hydrolysis: Under stirring at 1100 rpm, a 190 g / L titanyl sulfate solution was uniformly added to the reactor at a feeding rate of 1.5 mL / min, and the temperature of the reactor was kept constant at 90°C. The feeding time was 5 h, and the hydrolysis reaction ended when the feeding was completed;
[0038] S3. Preparation of metatitanic acid: Cool the hydrolyzed slurry to room temperature, wash with water, and dry at 120° C. for 10 h to obtain metatitanic acid;
[0039] S4. Preparation of Sodium Titanate: Sodium hydroxide and metatitanic acid were mixed in a sodium to titanium molar ratio of 2:3. The mixture was calcined under an argon atmosphere at a heating rate of 5°C / min to 850°C, held for 7 hours, and then naturally cooled to obtain sodium titanate. The synthesized sodium titanate had a particle size of 4-10 microns and excellent sphericity. The sodium titanate achieved a specific capacity of 113 mAh / g at 2000 mA / g, with a capacity retention of 81% after 1000 cycles.
[0040] Example 3
[0041] A method for preparing a low-cost sodium titanate negative electrode material from a titanyl sulfate solution, the preparation method comprising the following steps:
[0042] S1. Preheating of base liquid: Take appropriate amount of deionized water in the reactor and preheat it to 100℃;
[0043] S2. Hydrolysis: Under stirring at 1200 rpm, a 210 g / L titanyl sulfate solution was uniformly added to the reactor at a feeding rate of 1.2 mL / min, and the temperature of the reactor was kept constant at 100° C. The feeding time was 8 h. The hydrolysis reaction ended when the feeding was completed;
[0044] S3. Preparation of metatitanic acid: Cool the hydrolyzed slurry to room temperature, wash with water, and dry at 120° C. for 10 h to obtain metatitanic acid;
[0045] S4. Preparation of Sodium Titanate: Sodium acetate and metatitanic acid were mixed in a sodium to titanium molar ratio of 2:3. The mixture was calcined under an argon atmosphere at a heating rate of 5°C / min to 900°C, held for 10 hours, and then naturally cooled to obtain sodium titanate. The synthesized sodium titanate had a particle size of 1-6 microns and excellent sphericity. It achieved a specific capacity of 103 mAh / g at 2000 mA / g and a capacity retention of 86% after 1000 cycles.
[0046] Example 4
[0047] A method for preparing a low-cost sodium titanate negative electrode material from a titanyl sulfate solution, the preparation method comprising the following steps:
[0048] S1. Preheating of base liquid: Take an appropriate amount of deionized water in the reactor and preheat it to 110°C;
[0049] S2. Hydrolysis: Under stirring at 1400 rpm, a 240 g / L titanyl sulfate solution was uniformly added to the reactor at a feeding rate of 1.0 mL / min, and the temperature of the reactor was kept constant at 110° C. The feeding time was 12 h. The hydrolysis reaction ended when the feeding was completed;
[0050] S3. Preparation of metatitanic acid: Cool the hydrolyzed slurry to room temperature, wash with water, and dry at 120° C. for 10 h to obtain metatitanic acid;
[0051] S4. Preparation of Sodium Titanate: Sodium carbonate and metatitanic acid were mixed in a sodium to titanium molar ratio of 2:3. The mixture was calcined under an argon atmosphere at a heating rate of 5°C / min to 950°C, held for 5 hours, and then naturally cooled to obtain sodium titanate. The synthesized sodium titanate had a particle size of 6-10 microns and excellent sphericity. The sodium titanate achieved a specific capacity of 96 mAh / g at 2000 mA / g, with a capacity retention rate of 79.2% after 1000 cycles.
[0052] Example 5
[0053] A method for preparing a low-cost sodium titanate negative electrode material from a titanyl sulfate solution, the preparation method comprising the following steps:
[0054] S1. Preheating of base liquid: Take an appropriate amount of deionized water in the reactor and preheat it to 85°C;
[0055] S2. Hydrolysis: Under stirring at 1300 rpm, a 180 g / L titanyl sulfate solution was uniformly added to the reactor at a feeding rate of 1.6 mL / min, and the temperature of the reactor was kept constant at 85°C. The feeding time was 10 h, and the hydrolysis reaction ended when the feeding was completed;
[0056] S3. Preparation of metatitanic acid: Cool the hydrolyzed slurry to room temperature, wash with water, and dry at 120° C. for 10 h to obtain metatitanic acid;
[0057] S4. Preparation of Sodium Titanate: Sodium oxide and metatitanic acid were mixed in a sodium to titanium molar ratio of 2:3. The mixture was calcined under an argon atmosphere at a heating rate of 5°C / min to 850°C, held for 12 hours, and then naturally cooled to obtain sodium titanate. The synthesized sodium titanate had a particle size of 1-6 microns and excellent sphericity. It achieved a specific capacity of 106 mAh / g at 2000 mA / g and a capacity retention of 83% after 1000 cycles.
[0058] Example 6
[0059] A method for preparing a low-cost sodium titanate negative electrode material from a titanyl sulfate solution, the preparation method comprising the following steps:
[0060] S1. Preheating of base liquid: Take an appropriate amount of deionized water in the reactor and preheat it to 95°C;
[0061] S2. Hydrolysis: While stirring at 1150 rpm, a 220 g / L titanyl sulfate solution was uniformly added to the reactor at a feed rate of 1.3 mL / min, and the temperature of the reactor was kept constant at 95°C. The feeding time was 7 h, and the hydrolysis reaction ended when the feeding was completed;
[0062] S3. Preparation of metatitanic acid: Cool the hydrolyzed slurry to room temperature, wash with water, and dry at 120° C. for 10 h to obtain metatitanic acid;
[0063] S4. Preparation of Sodium Titanate: Sodium peroxide and metatitanic acid were mixed in a sodium to titanium molar ratio of 2:3. The mixture was calcined under an argon atmosphere at a heating rate of 5°C / min to 900°C, held for 8 hours, and then naturally cooled to obtain sodium titanate. The synthesized sodium titanate had a particle size of 1-5 microns and excellent sphericity. It achieved a specific capacity of 108 mAh / g at 2000 mA / g and a capacity retention of 85% after 1000 cycles.
[0064] Comparative Example 1
[0065] The method of preparing a traditional sodium titanate negative electrode material is to use anatase titanium dioxide (titanium dioxide) as a titanium source, calcine it with a sodium source, and then naturally cool it to obtain a sodium titanate negative electrode material.
[0066] The preparation method of anatase titanium dioxide is generally a sulfuric acid method, which includes the following steps:
[0067] S1. Ore preparation: crushing and magnetic separation of titanium ore;
[0068] S2. Preparation of titanium sulfate: using sulfuric acid to decompose titanium ore into TiOSO4;
[0069] S3, preparation of hydrated titanium dioxide: hydrolyzing TiOSO4 into TiO2·H2O;
[0070] S4, calcination: calcining the hydrolyzate into titanium dioxide;
[0071] S5. Post-processing: including surface treatment, separation and impurity removal to obtain titanium dioxide products.
[0072] After the titanyl sulfate solution is hydrolyzed into titanic acid, it goes through multiple energy-consuming steps such as calcination, surface treatment, and impurity removal. This process also produces wastewater, waste gas, and solid waste, which need to be treated to meet environmental protection standards, which also constitutes part of the cost.
[0073] In addition, the key link that affects the size, morphology and properties of the final product is the hydrolysis of the titanyl sulfate solution, that is, the reaction of titanyl sulfate with water to form hydrated titanium dioxide (metatitanic acid) precipitation and sulfuric acid:
[0074] TiOSO4+2H2O→TiO2·H2O+H2SO4
[0075] Currently, the hydrolysis process of titanyl sulfate requires precise control of multiple parameters, such as the acidity (pH value) of the solution. The particle size and morphology of titanic acid are also controlled by adding seed crystals or adjusting the hydrolysis conditions, which undoubtedly increases production costs.
[0076] In the preparation method of the present invention, sodium titanate is prepared by directly calcining metatitanic acid as a titanium source and a sodium source. Compared with the above-mentioned traditional method, multiple energy-consuming steps such as calcination, surface treatment, and impurity removal from metatitanic acid to titanium dioxide are omitted. In addition, the hydrolysis of titanyl sulfate does not require the addition of seed crystals and the adjustment of the system pH, which reduces the complexity of the operation and improves production efficiency. The obtained hydrolysis product metatitanic acid has good sphericity and more uniform particles.
[0077] Comparative Example 2
[0078] The metatitanic acid precursor was prepared by hydrolysis of industrial titanium liquid as titanium source.
[0079] Before the reaction, preheat the industrial titanium liquid and bottom water to 96 ° C respectively, and then use a peristaltic pump to uniformly add the titanium liquid to the three-necked flask containing bottom water within 16 minutes. After the addition is completed, heat the solution in the flask until it reaches a slightly boiling state (the first boiling point is 106 ° C) and observe the color change of the titanium liquid. When the titanium liquid turns steel gray, immediately turn off the heating and stirring, mature for 30 minutes, restart the heating and stirring after the maturity, and start the reaction timer when the titanium liquid reaches a slightly boiling state again (the second boiling point is 108 ° C). After 3 hours of reaction, add 10 mL of hot water, continue the reaction for 1 hour, turn off the heating and stirring, and cool the reacted slurry to about 45 ° C and vacuum filter the slurry to dry. Using Na2CO3 as the sodium source, 2g of titanate precursor was weighed according to n(Na):n(Ti) of 2:3, wherein the sodium source was in excess of 5% (mass fraction), 10mL of anhydrous ethanol was taken as a dispersant, added to a nylon ball mill, and ball milled in a high-speed ball mill for 2h. The slurry was taken out and placed in a surface dish, air-dried at room temperature to remove a large amount of anhydrous ethanol, and then placed in a 60℃ oven to dry for 90min. The dried material was scraped off and placed in a mortar to be fully ground. The mixed material was then transferred to a square porcelain boat, and the porcelain boat was placed in a muffle furnace and calcined in an air atmosphere. The calcination temperature was 800℃, the temperature was kept constant for 20h, and the heating / cooling rate was 5℃ / min.
[0080] The sodium titanate synthesized in Comparative Example 2 is mainly Na2Ti3O7 and Na2Ti6O 13The mixed phase has an initial discharge capacity of 233.77 mA·h / g at a low current density of 17.7 mA / g; after 200 cycles at a current density of 88.5 mA / g, the discharge capacity is 26.87 mA·h / g, the capacity retention rate is 47.56%, and the charge and discharge efficiency is 99.54%; the sodium storage process of the prepared mixed sodium titanate is dominated by pseudocapacitive behavior.
[0081] Although the method for synthesizing sodium titanate in Comparative Example 2 shortens the process for preparing sodium titanate, the hydrolysis process is too complicated and the electrochemical performance of the synthesized material is poor.
[0082] Experimental results and analysis
[0083] Figure 1 This is a SEM spectrum of metatitanic acid, a hydrolysis product in Example 1 of the present invention; Figure 2 The XRD spectrum of the hydrolysis product metatitanic acid in Example 1 of the present invention is shown. It can be seen that the metatitanic acid in Example 1 has good sphericity and uniform particles, with a particle size of approximately 1-5 microns. Metatitanic acid corresponds to the anatase titanium dioxide phase.
[0084] Figure 3 This is a SEM spectrum of sodium titanate prepared in Example 1 of the present invention; Figure 4 This is the XRD spectrum of sodium titanate prepared in Example 1 of the present invention; it can be seen that the sodium titanate prepared in Example 1 is a spherical nanoflower stacked with nanorods and nanosheets, and sodium titanate is mainly composed of Na2Ti3O7 and Na2Ti6O 13 In addition, there is a mixed phase of Na2SO4.
[0085] Figure 5 This is a performance diagram of the sodium titanate negative electrode prepared in Example 1 of the present invention after 200 cycles at 200 mA / g. It can be seen that the capacity retention rate of the sodium titanate negative electrode prepared in Example 1 is 86% after 200 cycles at 200 mA / g.
[0086] Figure 6 This is a performance diagram of the sodium titanate negative electrode prepared in Example 1 of the present invention after 1000 cycles at 2000 mA / g. It can be seen that the sodium titanate negative electrode prepared in Example 1 achieves a capacity retention rate of 78.4% after 1000 cycles at 2000 mA / g.
[0087] Figure 7 This is a rate performance diagram of the sodium titanate negative electrode prepared in Example 1 of the present invention. It can be seen that the sodium titanate negative electrode prepared in Example 1 achieves a specific capacity of 82 mAh / g at 2000 mA / g.
[0088] In summary, the beneficial effects brought about by the technical solution of the present invention are as follows:
[0089] 1. The present invention directly hydrolyzes a titanyl sulfate solution at a constant temperature and speed to produce metatitanic acid without the need for seed crystals or pH adjustment. This reduces operational complexity and improves production efficiency. The resulting hydrolyzed metatitanic acid exhibits excellent sphericity and uniform particles.
[0090] 2. The present invention directly uses metatitanic acid as a source of titanic acid and sodium to calcine and prepare sodium titanate, omitting multiple energy-consuming steps such as calcination, surface treatment, and impurity removal from metatitanic acid to titanium dioxide, greatly reducing the production cost of sodium titanate and having great economic benefits.
[0091] 3. The sodium titanate negative electrode material prepared by the present invention has excellent performance, achieving a specific capacity of sodium titanate of more than 82 mAh / g at 2000 mA / g, and a capacity retention rate of more than 78.4% after 1000 cycles.
[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing low-cost sodium titanate negative electrode material from titanyl sulfate solution, the preparation method comprising the following steps: S1. Preheating of base liquid: Take an appropriate amount of deionized water into the reaction kettle and preheat it to 80℃-110℃; S2, hydrolysis: under stirring, adding titanyl sulfate solution into the reactor at a uniform speed, and keeping the temperature of the system in the reactor constant. When the feeding is completed, the hydrolysis reaction is completed; S3, preparing metatitanic acid: cooling the hydrolyzed slurry to room temperature, washing with water, and drying to obtain metatitanic acid; S4. Preparation of sodium titanate: uniformly mix a sodium source and metatitanic acid in a sodium to titanium molar ratio of 2:3, calcine under an argon atmosphere, and then cool naturally to obtain sodium titanate.
2. The method for preparing low-cost sodium titanate negative electrode material from titanyl sulfate solution according to claim 1, characterized in that: The stirring speed in step S2 is 1000-1400 rpm.
3. The method for preparing low-cost sodium titanate negative electrode material from titanyl sulfate solution according to claim 1, characterized in that: The concentration of the titanyl sulfate solution in step S2 is 170-240 g / L.
4. The method for preparing low-cost sodium titanate negative electrode material from titanyl sulfate solution according to claim 1, characterized in that: The titanyl sulfate solution feed rate in step S2 is 1.0-1.8 mL / min.
5. The method for preparing low-cost sodium titanate negative electrode material from titanyl sulfate solution according to claim 1, characterized in that: The feeding time of the titanyl sulfate solution in step S2 is 2-12 hours.
6. The method for preparing low-cost sodium titanate negative electrode material from titanyl sulfate solution according to claim 1, characterized in that: In step S3, the drying temperature is 120° C. and the drying time is 10 hours.
7. The method for preparing low-cost sodium titanate negative electrode material from titanyl sulfate solution according to claim 6, characterized in that: In step S4, the sodium source is one or more of sodium acetate, sodium carbonate, sodium hydroxide, sodium oxalate, sodium oxide, and sodium peroxide.
8. The method for preparing low-cost sodium titanate negative electrode material according to any one of claims 1 to 7, characterized in that: The calcination in step S4 is as follows: heating to 800-950° C. at a heating rate of 5° C. / min and keeping the temperature for 5-15 hours.
Citation Information
Patent Citations
Method for preparing spherical lithium titanate from inorganic titanium sources
CN102153137A
Method for preparing lithium titanate from inorganic titanium source, product and application
CN108529666A
Production of sodium hexatitanate lumpy powder particle and cosmetic raw material using sodium hexatitanate lumpy powder particle
JP1999130433A
Process of preparing alkali metal titanates
US20110278495A1